2021
DOI: 10.1177/1745691621990628
|View full text |Cite
|
Sign up to set email alerts
|

Belief in Unconscious Repressed Memory Persists

Abstract: On the basis of converging research, we concluded that the controversial topic of unconscious blockage of psychological trauma (i.e., repressed memory) remains very much alive in clinical, legal, and academic contexts. In his commentary, Brewin (this issue, p. 443) conducted a cocitation analysis and concluded that scholars do not adhere to the concept of unconscious repression. Furthermore, he argued that previous survey research did not specifically assess unconscious repression. Here, we present critical ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 37 publications
1
28
0
Order By: Relevance
“…In the same vein, they also strongly agreed that the humans' mind is capable to unconsciously block traumatic memories prior to recovering them. As it stands now, beliefs concerning dissociative amnesia were widespread and in line with recent work showing strong beliefs in repressed memory (e.g., Ost et al, 2013Ost et al, , 2017Otgaar, Howe, Dodier, et al, 2021;Patihis et al, 2014). Indeed, by roughly matching our items with those usually used in previous research (e.g., "Traumatic memories are often repressed"; Otgaar et al, 2020), one can reach the conclusion that beliefs in repressed memory and dissociative amnesia are, to some extent, very much alike.…”
Section: On the Relationship Between Claiming And Believing In Dissociative Amnesiasupporting
confidence: 87%
See 3 more Smart Citations
“…In the same vein, they also strongly agreed that the humans' mind is capable to unconsciously block traumatic memories prior to recovering them. As it stands now, beliefs concerning dissociative amnesia were widespread and in line with recent work showing strong beliefs in repressed memory (e.g., Ost et al, 2013Ost et al, , 2017Otgaar, Howe, Dodier, et al, 2021;Patihis et al, 2014). Indeed, by roughly matching our items with those usually used in previous research (e.g., "Traumatic memories are often repressed"; Otgaar et al, 2020), one can reach the conclusion that beliefs in repressed memory and dissociative amnesia are, to some extent, very much alike.…”
Section: On the Relationship Between Claiming And Believing In Dissociative Amnesiasupporting
confidence: 87%
“…Of importance, despite being highly criticised (e.g., , the idea and related beliefs concerning unconscious repressed memory are intrinsically widespread. Survey studies have found that both laypeople and professionals believe that the human mind is able to unconsciously block memories for traumatic events and that repressed memories can be accurately retrieved in therapy (see Ost et al, 2013Ost et al, , 2017Otgaar, Howe, Dodier, et al, 2021;Patihis et al, 2014). However, these survey studies have not specifically asked about the existence of dissociative amnesia and instead focused more on the belief of repressed memory.…”
Section: Controversial Aspects Surrounding Dissociative Amnesiamentioning
confidence: 99%
See 2 more Smart Citations
“…We also tested whether participating in and being debriefed from a false memory study would improve participants understanding of how memory works (Murphy et al, 2020). There has been much discussion in the empirical literature about people's understanding of memory accuracy and malleability (Brewin et al, 2019;Otgaar et al, 2021). In daily life, through online news or social interaction, people are frequently exposed to misinformation.…”
Section: The Current Studiesmentioning
confidence: 99%